LoRaWISEP+: A Comprehensive Tool for Strategic Gateway Placement in LoRaWAN Networks - Abreu, Pedro F. F.; Mendes, Luís H. de O.; Sarmento Neto, Geraldo A.; Silva, Thiago A. R. da; Veloso, Artur F. da S.; Leão, Erico; dos Reis Junior, José V. (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2024)
The Internet of Things has revolutionized device interconnectivity, with Low Power Wide Area Networks (LPWAN) enabling long-range communication with minimal energy consumption. Within this context, LoRaWAN is widely recognized as an efficient and robust technology for LPWAN networks. However, strategic gateway deployment remains a challenging for optimizing network performance. In this way, this paper issue proposes LoRaWISEP+, an enhanced version of the LoRaWISEP system, consisting of a comprehensive tool designed to improve the deployment process of LoRaWAN gateways. This solution incorporates additional clustering algorithms, such as K-Medoids (KMD) and Fuzzy C-Means (FCM), and a redesigned userfriendly interface, facilitating optimal placement of gateways and improving overall network coverage and reliability. In order to validate the new features of the proposed tool, a thorough evaluation was conducted using real-world deployment scenarios. Results demonstrate that different clustering algorithms exhibit strengths in specific characteristics, such as FCM being more suitable for lower energy consumption and K-Means (KM) being more suitable for higher transmission rates. This makes LoRAWISEP+ an enabling tool for optimizing network planning according to the most beneficial characteristic for the user.